Pretreatment DCE-MRI-Based Deep Learning Outperforms Radiomics Analysis in Predicting Pathologic Complete Response to Neoadjuvant Chemotherapy in Breast Cancer - Peng, Yunsong; Cheng, Ziliang; Gong, Chang; Zheng, Chushan; Zhang, Xiang; Wu, Zhuo; Yang, Yaping; Yang, Xiaodong; Zheng, Jian; Shen, Jun (Frontiers in Oncology, 2022)
Purpose: To compare the performances of deep learning (DL) to radiomics analysis (RA) in predicting pathological complete response (pCR) to neoadjuvant chemotherapy (NAC) based on pretreatment DCE-MRI in breast cancer. Materials and Methods: This retrospective study included 356 breast cancer patients who underwent DCE-MRI before NAC and underwent surgery after NAC. Image features and kinetic parameters of tumors were derived from DCE-MRI. Molecular information was assessed based on immunohistochemistry results. The image-based RA and DL models were constructed by adding kinetic parameters or molecular information to image-only linear discriminant analysis (LDA) and convolutional neural networks (CNN) models. The predictive performances of developed models were assessed by receiver operating curve (ROC) analysis and compared with the DeLong method. Results: The overall pCR rate was 23.3% (83/356). The area under the ROC (AUROC) of the image-kinetic-molecular RA model was 0.781 (95% confidence interval [CI]: 0.735, 0.828), which was higher than that of the image-kinetic RA model (0.629, 95% CI: 0.595, 0.663; P<0.001) and comparable with that of the image-molecular RA model (0.755, 95% CI: 0.708, 0.802; P=0.133). The AUROC of the image-kinetic-molecular DL model was 0.83 (95% CI: 0.816, 0.847), which was higher than that of image-kinetic and image-molecular DL models (0.707, 95% CI: 0.654, 0.761; 0.79, 95% CI: 0.768, 0.812; P<0.001) and higher than that of the image-kinetic-molecular RA model (0.778, 95% CI: 0.735, 0.828; P<0.001). Conclusions: The pretreatment DCE-MRI-based DL model is superior to the RA model in predicting pCR to NAC in breast cancer patients. The image-kinetic-molecular DL model has the best prediction performance.